Penularan Emosional (Emotional Contangion) Kajian Literatur dan Rekomendasi - Santoso, Agus; Sari, Dita Kurnia (Jurusan Bimbingan dan Konseling Islam, 2021)
Much evidence describes the phenomenon of the transmission of emotions from one person to another. Emotional contagion refers to the process of transferring emotions and behaviors between individuals. Even though there is a lot of research on this, most of it is still applicable. This study aims to provide a conceptual framework related to emotional contagion. The research method used is the library research method. The data collection method used is the documentation method. The data analysis technique used is content analysis. To maintain the accuracy of the assessment and prevent misinformation in data analysis, inter-library checking and library re-reading were carried out. The result of this study is a comprehensive study of emotional transmission, including: (1) a definition of emotional transmission; (2) an explanation of emotional contagion mechanisms; (3) factors influencing emotional transmission; and (4) forms of emotional transmission. This research also provides suggestions for controlling and managing the contagion of negative emotions